Law and the Quest for Equality - Thurgood Marshall (Washington University Law Quarterly, 1967)
I have defined my subject as “Law and the Quest for Equality.” Actually the subject involves several themes: the synergy of law and social patterns; the promotion of reform through, and by means of, existing legal means and doctrine; and the changing role of a lawyer in society. I shall begin by giving a brief exegesis of the School Segregation Cases. I do not propose to tell of every legal recognition of equality or of every lapse or legitimization of inequality from Dred Scott' to the school cases; the story has been told elsewhere and quite well. But it is necessary for the development of my subject and themes to discuss some of these cases.
Keywords: Civil rights; Equal protection